Sistem Pendukung Keputusan Pemilihan Hotel Terbaik Menggunakan Metode WASPAS dan Pembobotan ROC - Dwiparaswati, Windy (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Choosing the best hotel is often a challenge for travelers because many criteria must be considered such as price, facilities, location, and services. To overcome these problems, this study developed a decision support system (DSS) using Weighted Aggregate Product Sum Assessment (WASPAS) and Rank Order Central Weighting (ROC).The WASPAS method was chosen because it has the ability to combine the advantages of the weighted sum model (WSM) and the weighted product model (WPM), resulting in a more accurate and efficient decision.While the ROC method is used to determine the weight of each criterion objectively based on the importance of these criteria. From the calculation results, Hotel C ranks highest with a value of 0.877, indicating that this hotel meets the predetermined criteria better than other alternatives. In addition, other hotels such as Hotel A and Hotel D also performed quite well, occupying the second and third positions.